Telaah Tematik Terhadap Hadis-Hadis Mengenai Pilihan Hidup Tanpa Anak (Childfree) dalam Prespektif Islam - Arif Hidayatullah; Ahmad Fudhaili (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The childfree phenomenon in contemporary Muslim social discourse has sparked debate regarding its legal status, particularly from the perspective of hadith as the second authoritative source in Islam. This study aims to examine the extent to which the hadith of the Prophet Muhammad addresses phenomena related to reproductive regulation and the childfree phenomenon. This study uses a qualitative literature review with a thematic (maudhu'i) approach to hadith. Hadiths were collected based on indicators of the causes of childfree obtained from contemporary academic literature, while the primary literature for hadith sources came from the nine main hadith books, kutub al-tis'ah. The results of this study indicate that the hadiths of the Prophet Muhammad SAW explicitly reject narratives that reduce childbirth to an economic burden, an ecological threat, or a source of suffering that must be avoided. Instead, they affirm childbirth as part of a meaningful divine plan, accompanied by guarantees of sustenance, protection of basic rights, and ethical mechanisms to correct imbalances of responsibility within the family. Although Islam acknowledges the reality of the global crisis and provides flexibility through the permissibility of 'azl and consideration of women's physical and mental health, this flexibility does not mean legitimizing the childfree ideology based on philosophical antinatalism. Hadiths about nature, destiny, and the purpose of encouraging procreation affirm Islam's pronatalist orientation, which places reproductive decisions within the framework of moral responsibility, social relations, and the sustainability of the humanitarian mission, so that the childfree choice can only be understood in a limited and contextual manner, not as a normative principle that negates the value of birth.